Study on Cu2ZnSnSe4 crystals and heterojunctions on their basis - Kovaliuk, T. T.; Maistruk, E. V.; Solovan, M. N.; Koziarskyi, I. P.; Maryanchuk, P. D. (Technology and design in electronic equipment, 2018)
The most promising materials for the solar radiation converters are such compounds as CdTe and Cu(In, Ga)Se2, CuIn(S, Se)2, CuGa(S, Se)2 solid solutions. However, the uneconomic nature of Cd, Te and the limited supply of In and Ga, as well as their high cost, force researchers to replace In and Ga with the more common elements of II and IV groups, namely Zn and Sn. Apart from that, researchers are now testing such new semiconductor compounds as ZnSnS4, Cu2ZnSnSe4, and solid solutions on their basis. These compounds have a band gap width (Eg ≈ 1.5 eV) close to optimal for the conversion of solar energy, a high light absorption coefficient (≈ 105cm–1), a long lifetime and a high mobility of charge carriers. Moreover, the interest in such semiconductor heterojunctions as TiO2/ZnSnS4, which have several advantages over homo-transitions, is steadily growing at present. The paper presents results studies of kinetic properties of Cu2ZnSnSe4 crystals. We fabricated n-TiO2/p-Cu2ZnSnSe4 anisotype heterojunctions, determined their main electrical parameters and built their energy diagram. The Cu2ZnSnSe4 crystals have p-type conductivity and the Hall coefficient practically independent of temperature. The temperature dependence of the electrical conductivity σ for Cu2ZnSnSe4 crystalsis metallic in character, i. e. σ decreases with increasing temperature, which is caused by a decrease in the mobility of the charge carriers with the growth of T. Thermoelectric power for the samples is positive, which also indicates the prevalence of p-type conductivity. In this study, the n-TiO2/p-Cu2ZnSnSe4 heterojunctions were produced by reactive magnetron sputtering of a thin TiO2 film on the Cu2ZnSnSe4 substrate. The energy diagram of the investigated n-TiO2/p-Cu2ZnSnSe4 anisotype heterojunctions was constructed in accordance with the Anderson model, without taking into account the surface electrical states and the dielectric layer, based on the values of the energy parameters of semiconductors determined experimentally and taken from literary sources. The authors have also investigated electrical properties of the heterojunctions: the value of the potential barrier was determined, the value of the series resistance and shunt resistance (respectively, Rs = 8 W and Rsh = 5.8 kW) at room temperature. The dominant mechanisms of current transfer were established: tunneling-recombination mechanism in the voltage range from 0 to 0.3 V, and over-barrier emission and tunneling with inverse displacement in the voltage range from 0.3 to 0.45 V.